Impacts of Consumer-Brand Identification for Strengthening the Sustainability of Malaysian Fashion Brands - Siti Fatimah Hashim; Rosita Mohd. Tajudin; Ameer Shakir Zainol (International Journal of Supply Chain Management, 2018)
The study is to examine the impact of consumer-brand identification (CBI) to strengthen the sustainability of Malaysian Fashion Brands (MFBs) that are facing competitive fights in the marketplace. A report showed that approximately 90% of MFBs that falls in SME category have to close down their businesses due to lacking in consumer-brand relationship as a competitive edge. The study had developed an integrated framework where CBI as the independent variable and Brand Loyalty as the dependent variable in creating consistent high values positively perceived through Brand Community that serves as a mediator. The moderating effect of individual heterogeneity of brand preferences among MFB consumers also being examined. The data was collected from 115 respondents of MFBs consumers by using non-probability sampling of convenient and snowball sampling techniques. A causal model was developed and tested in SEM-PLS and the results indicated that there was no significant relationship between CBI and brand loyalty however, brand community potentially full mediated the relationship of CBI and brand loyalty as well as individual heterogeneity moderated significantly the relationship. Future implications and limitations of the research study were discussed based on the research findings.